Association of plasma Alzheimer's disease biomarkers with cognitive decline in cognitively unimpaired individuals - Cogswell, Petrice M.; Wiste, Heather J.; Therneau, Terry M.; Griswold, Michael E.; Mattsson-Carlgren, Niklas ; 0000-0002-8885-7724; Palmqvist, Sebastian ; 0000-0002-9267-1930; Binette, Alexa Pichet; Stomrud, Erik ; 0000-0002-0841-5580; Bateman, Randall J.; Barthelemy, Nicolas; Braunstein, Joel B.; West, Tim; et al. (Alzheimer's and Dementia, 2025)
INTRODUCTION: Plasma biomarkers’ utility for predicting incident mild cognitive impairment (MCI) remains unclear. We evaluated associations of plasma Alzheimer's disease (AD) biomarkers and amyloid positron emission tomography (PET) with transitions from cognitively unimpaired (CU) to MCI in the Mayo Clinic Study of Aging (MCSA) and BioFINDER-2 studies. METHODS: Associations of continuous baseline plasma biomarker levels and amyloid PET Centiloid with progression to MCI, adjusting for age, sex, and education, were evaluated with Cox proportional hazards models. RESULTS: The study included 381 MCSA and 584 BioFINDER-2 participants. Amyloid PET and percent phosphorylated to non-phosphorylated tau217 (%p-tau217) were strong predictors of progression to MCI in both cohorts: hazard ratios of 1.49 and 1.23 in the MCSA and 1.72 and 1.65 in BioFINDER, respectively. Amyloid beta 42/40 was a significant predictor in BioFINDER-2 only (hazard ratio 2.20). DISCUSSION: Plasma %p-tau217 was associated with progression from CU to MCI in both cohorts, although differences in biomarker associations may be related to differences in the two cohorts. Highlights: Mass-spectrometry-based plasma phosphorylated tau217 was associated with cognitively unimpaired to mild cognitive impairment (MCI) progression. Plasma amyloid beta 42/40 was a significant predictor in BioFINDER but not the Mayo Clinic Study of Aging (MCSA). Amyloid positron emission tomography (PET) was the strongest predictor of progression to MCI in the MCSA. Plasma had added value to amyloid PET in BioFINDER but not the MCSA. Biomarker performance may vary with cohort and biomarker measurement differences.
Keywords: Alzheimer's disease; amyloid beta 42/40; amyloid beta positron emission tomography; mild cognitive impairment; phosphorylated tau 217; plasma biomarkers